Assessing Hydrological Alteration Caused by Climate Change and Reservoir Operations in the San Joaquin River Basin, California - Maskey, Mahesh L.; Facincani Dourado, Gustavo; Rallings, Anna M.; Rheinheimer, David E.; Medellín-Azuara, Josué; Viers, Joshua H. (Frontiers in Environmental Science, 2022)
Freshwater aquatic ecosystems are highly sensitive to flow regime alteration caused by anthropogenic activities, including river regulation and atmospheric warming-induced climate change. Either climate change or reservoir operations are among the main drivers of changes in the flow regime of rivers globally. Using modeled unregulated and simulated regulated streamflow under historical and future climate scenarios, this study evaluated potential changes to the flow regime due to climate change and reservoir operations for the major tributaries of the San Joaquin River Basin, California USA. We selected a set of Indicators of Hydrologic Alteration (IHA) to evaluate historical and projected future trends of streamflow dynamics: rise and fall rates, durations and counts of low and high pulses, and the magnitude of extremes. Results show that most indicators have pronounced departures from baseline conditions under anticipated future climate conditions given existing reservoir operations. For example, the high pulse count decreases during regulated flow conditions compared to increased frequency under unregulated flow conditions. Finally, we observed a higher degree of flow regime alteration due to reservoir operations than climate change. The degree of alteration ranges from 1.0% to 9.0% across the basin among all future climate scenarios, while reservoir operations alter the flow regime with a degree of alteration from 8.0% to 25%. This study extends multi-dimensional hydrologic alteration analysis to inform climate adaptation strategies in managed river systems.